2005
DOI: 10.1038/sj.bjc.6602631
|View full text |Cite
|
Sign up to set email alerts
|

HOXB13 is downregulated in colorectal cancer to confer TCF4-mediated transactivation

Abstract: Mutations in the Wnt signalling cascade are believed to cause aberrant proliferation of colorectal cells through T-cell factor-4 (TCF4) and its downstream growth-modulating factors. HOXB13 is exclusively expressed in prostate and colorectum. In prostate cancers, HOXB13 negatively regulates b-catenin/TCF4-mediated transactivation and subsequently inhibits cell growth. To study the role of HOXB13 in colorectal tumorigenesis, we evaluated the expression of HOXB13 in 53 colorectal tumours originated from the dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
84
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 39 publications
5
84
0
Order By: Relevance
“…The implication of the HOXB13 gene product in different types of cancer is beginning to be elucidated. It has been proposed as a marker for prostate cancer [18], and is also believed to be involved in endometrial cancer [19], cervical cancer [20], as well as renal cell carcinoma [21], and colorectal cancer [22]. In human cutaneous malignant melanoma with distant metastasis, the expression level of certain HOX genes, including HOXB13, was higher than in those melanoma patients without metastases [23], and in endometrial cancer cells, antisense-transfection of the HOXB13 gene reduced the invasive ability of the cells [19].…”
Section: Discussionmentioning
confidence: 99%
“…The implication of the HOXB13 gene product in different types of cancer is beginning to be elucidated. It has been proposed as a marker for prostate cancer [18], and is also believed to be involved in endometrial cancer [19], cervical cancer [20], as well as renal cell carcinoma [21], and colorectal cancer [22]. In human cutaneous malignant melanoma with distant metastasis, the expression level of certain HOX genes, including HOXB13, was higher than in those melanoma patients without metastases [23], and in endometrial cancer cells, antisense-transfection of the HOXB13 gene reduced the invasive ability of the cells [19].…”
Section: Discussionmentioning
confidence: 99%
“…HOXB13 has been found to negatively regulate wound healing possibly by down-regulating hyaluronic acid (41, 42). HOXB13 was found to be down-regulated in prostate and colorectal cancer cells, where it has an antiproliferative role (43,44). More recently, HOXB13 was found to be epigenetically inactivated in a subset of renal cell carcinomas and had growthinhibitory effects in vitro (45).…”
Section: Discussionmentioning
confidence: 99%
“…The dysregulation of Hox genes may affect various pathways that play critical roles in tumorigenesis and cancer metastasis (19). Evidence shows that ectopic expression of HoxB13 in prostate and colon cancer cells can suppress tumor growth through downregulating of ÎČ-catenin-TCF pathway (17,23). It has been shown that HoxD10 expression is reduced in both breast and endometrial tumors (24).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their roles in development, numerous Hox genes (HoxB13, HoxA5 and HoxC6) have been found to be expressed aberrantly in a variety of solid tumors, including breast, colon and prostate cancers (16)(17)(18)(19)(20). Emerging evidence suggests that the expression of Hox genes is under epigenetic control (19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%